The versatile strategies of Escherichia coli pathotypes: a mini review - Sousa,C. P. (2006)
The widespread species Escherichia coli includes a broad variety of different types, ranging from highly pathogenic strains to avirulent isolates. Few microorganisms are as versatile as E. coli. Pathogenic strains remain a leading cause of severe and persistent infant diarrhea in developing countries. They may be limited to colonization of a mucosal surface or can disseminate throughout the body and have been implicated in urinary tract infection, sepsis/meningitis and gastrointestinal infection. The human gastrointestinal tract is susceptible to diarrheagenic E. coli infections. Escherichia coli have effectively managed to subvert the host cytoskeleton for their own purposes causing substantial diarrheal disease, a major public health problem worldwide. This review deals with the different strategies regarding E. coli as a pathogen and the virulence traits of its pathotypes highlighting the species as a commensal, opportunistic and specialized pathogen.